Strategic tools and methods for promoting hospitality and tourism services - Nedelea, Alexandru, 1971-; Korstanje, Maximiliano; George, Babu P. (Hershey, PA : Business Science Reference, 2016)
'This book provides interdisciplinary perspectives in the areas of global tourism and hospitality, highlighting cultural boundaries of strategic knowledge management through the use of case studies and theoretical research'--
Includes bibliographical references and index.
Keywords: Tourism -- Marketing